Peranan Sistem Pengendalian Intern Modal Kerja Terhadap Efisiensi Dan Efektifitas Perusahaan Studi Kasus pada Perusahaan Perseorangan MITRA ANDA - Muanas, Muanas; Tedyanto, Agustono (Jurnal Ilmiah Ranggagading (JIR), 2011)
Amid tight competition within the current global crisis, requiring the company to expand its field of business in order to maintain the companys survival. How to maintain the business is to make decisions based on objective inputs, hence the need for an accounting information system. One of the systems that affect the company is successful in the cash management system, namely the cycle and the cash receipts and disbursements for the necessary control and supervision. This is what lies behind this final, because the company requires an evaluation to identify and to realize a good control system over cash receipts and payments systems in the company. This final project aims to: (1) To determine the condition of working capital in the company and role in the cycle of working capital expenditures and cash receipts in the Company Individual Your Partner. (2) To determine the role of the internal control system of working capital in the Company Individual Your Partner. Data collection techniques in the writing of this final interview, observation, and documentation. In preparing this paper, the authors choose Individual Company Your Partner as a research object which is located at highway Km.17 Parung Bogor. To obtain data about the process of cash receipts and disbursements, implementation of internal audit and the role of the company, the research uses a Research Library is reading books related to issues discussed and research methods that the authors come to the Field Research Company Individual Your Partner Direct to obtain the necessary data. Based on research results obtained from the authors note that internal control of the Company Individual Your Partner is a function of the independent assessments to test and evaluate the organization activities, with the aim of providing advice and recommendations to management about the efficiency and effectiveness of operations implemented. This is supported by the organizational structure of companies that have separate departments that direct organizations led by the chief executive. Based on the analysis results can be recommended to the Company Individual Your Partners, namely: (1) With the increasingly rapid growth of the company, it needs to be supported by the infrastructure is better if need be added, in order to increase sales volume capacity to provide the best services to customers of the company a way to add new vehicles to the faster delivery and to meet all requests from customers, (2) To retain existing customers and prospective customers in an effort to find new, there should be a policy of targeted marketing strategies and efficiency and seek supervision of eg with the policy to intensify the campaign either through sales promotion with banners or company, (3) To improve the marketability and collectibility, private companies need to do your Partner to the state of the market share analyzing the current economic conditions. In addition, it is also necessary to improve the customer satisfactory service. Like warm-hearted, courteous, always gives a good impression by smiling and saying hello.